The effect of palm oil diesel fuel contaminated lubricant on sliding wear of cast irons against mild steel - Masjuki, H.H.; Maleque, Md. Abdul (Elsevier BV, 1996)
The effect of various percentages of palm oil diesel (POD) fuel contaminated lubricants on the wear charactefis:ics of east irons during sliding contact was investigated. This was done on three types of cast iron, namely spheroidal graphite, flake graphite and chilled cast iron against a mild steel disc configuration using a pin-on-disc type of friction and wear apparatus. The lubricants used for the test specin',~n were Maeh 5 SAE 40 with various percentages of POD. For comparison purposes, pure diesel engine lubricant oil and pure palm oil diesel were also used as lubricants. The test conditions were as follows: pressure, 1 MPa; sliding speed, 0.2 m s-t; sliding distance, 56 km; room temperature, -- 30 °C. It was observed that the addition of 5% palm oil diesel into the engine lubricant improves the performance of the lubricant in terms of anti-wear characteristics, reducing the wear rate of cast irons. The use of pure commercial (0% POD contamination) lubricant resulted in a moderate wear rate, whilst pure POD (100%) lubricant produced the highest wear rate compared with the other combinations of contaminated lubricants.